Modelling the global economic consequences of a major African swine fever outbreak in China - Mason-D’Croz, Daniel; Bogard, Jessica R.; Herrero, Mario; Robinson, Sherman; Sulser, Timothy B.; Wiebe, Keith D.; Willenbockel, Dirk; Godfray, H. Charles J. (Nature Publishing Group, 2020)
African swine fever is a deadly porcine disease that has spread into East Asia where it is having a detrimental effect on pork production. However, the implications of African swine fever on the global pork market are poorly explored. Two linked global economic models are used to explore the consequences of different scales of the epidemic on pork prices and on the prices of other food types and animal feeds. The models project global pork prices increasing by 17–85% and unmet demand driving price increases of other meats. This price rise reduces the quantity of pork demanded but also spurs production in other parts of the world, and imports make up half the Chinese losses. Demand for, and prices of, food types such as beef and poultry rise, while prices for maize and soybean used in feed decline. There is a slight decline in average per capita calorie availability in China, indicating the importance of assuring the dietary needs of low-income populations. Outside China, projections for calorie availability are mixed, reflecting the direct and indirect effects of the African swine fever epidemic on food and feed markets.